Analysis Of The Role Of Journalistic Language In Building A Balanced Legal News Narrative - Rokibullah, Rokibullah (Publikasi Indonesia, 2023)
Legal news has a crucial role in providing information and understanding to the public about ongoing legal cases. However, often the news can be affected by certain biases or viewpoints, which can affect the objectivity of the news narrative. Therefore, this study aims to analyze the role of journalistic language in building balanced legal news narratives, by considering aspects of objectivity and equality of information. The research method in this study is qualitative. The data collection technique was carried out by literature study obtained from Google Schoolar and legal news articles published in the 2020-2023 period in various trusted mass media. The data that has been collected will be analyzed qualitatively using content analysis techniques. The results showed that a balanced legal news narrative must meet specific criteria, including prioritizing fairness, accuracy, and neutrality in the delivery of information. Democratic journalistic language avoids differences in level or rank in the use of language and prioritizes active sentences to be more easily understood by readers. In addition, journalistic language must also adhere to standard language rules and ethics to reflect honesty, sincerity and respect for individual privacy. By adhering to these criteria, legal news narratives can be considered balanced, able to provide a comprehensive picture, and respect the interests of society as a whole.